Critical Discourse Analysis and the Cultivation of Critical Reading Ability - Yizhen, Luo (International Journal of Emerging Trends in Social Sciences, 2019)
As an important part of English learning, English reading should not only focus on the input of language knowledge, but also the cultivation of critical language awareness and critical thinking model. The traditional English reading model usually includes vocabulary learning, background knowledge introduction and text analysis, which is limited to letting students understand the literal meaning and some implicit information of the text. However, critical discourse analysis provides a broader perspective for readers. Based on the theory of systemic-functional linguistics, this paper takes an article from Chinese first-year college English textbooks as corpus to conduct a critical discourse analysis and expose the ideology behind the text. The analysis found that the article is not simply a report on a war, but also a tribute to the British society. It helped England gain sympathy from the international community by exposing the cruel and inhuman acts of the German Nazis in Britain. At the same time, it praised the British government for its strong resistance against German aggression and complimented the united British people. This paper aims to explore the methods of combining critical discourse analysis and reading teaching, and put forward suggestions for Chinese reading teaching and the cultivation of students’ critical reading ability.